THEORETICAL-GNOSEOLOGICAL AND PRACTICAL ANALYSIS OF DIALOGICAL AND INTERACTIVE LOGIC SYSTEMS - Majidova Oysafar Umarovna (Bright Mind Publishing, 2025)
This article explores the theoretical-gnoseological and practical aspects of dialogical and interactive logic systems within the framework of modern cognitive science and artificial intelligence. The study aims to understand how dialogical logic facilitates dynamic knowledge formation, mutual understanding, and reasoning, while interactive logic systems bridge human-machine communication. The research draws from classical gnoseology, constructivist epistemology, and computational logic paradigms to propose an integrated model for dialogical reasoning in modern interactive environments.
Keywords: Dialogical logic, interactive systems, gnoseology, epistemology, cognitive modeling, artificial intelligence, reasoning, communication theory, pragmatics, human-machine interaction.